Space-based and object-centered gaze cuing of attention in right hemisphere-damaged patients - Dalmaso, Mario; Castelli, Luigi; Priftis, Konstantinos; Buccheri, Marta; Primon, Daniela; Tronco, Silvia; Galfano, Giovanni (Frontiers in Psychology, 2015)
Gaze cuing of attention is a well established phenomenon consisting of the tendency to shift attention to the location signaled by the averted gaze of other individuals. Evidence suggests that such phenomenon might follow intrinsic object-centered features of the head containing the gaze cue. In the present exploratory study, we aimed to investigate whether such object-centered component is present in neuropsychological patients with a lesion involving the right hemisphere, which is known to play a critical role both in orienting of attention and in face processing. To this purpose, we used a modified gaze-cuing paradigm in which a centrally-placed head with averted gaze was presented either in the standard upright position or rotated 90° clockwise or anti-clockwise. Afterwards, a to-be-detected target was presented either in the right or in the left hemifield. The results showed that gaze cuing of attention was present only when the target appeared in the left visual hemifield and was not modulated by head orientation. This suggests that gaze cuing of attention in right hemisphere-damaged patients can operate within different frames of reference.